A Systematic Review Of The Leadership Style Influence, Managerial Support, And Work Environment On Employee Performance Through Work Motivation As An Intervening - Anindya, Dara; Soetjipto, Budi Eko; Wardhana, Ludi Wisnu (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
This study aims to conduct a systematic review of the influence of leadership style, managerial support, and work environment on employee performance, with work motivation serving as an intervening variable. The review adopts a Systematic Literature Review (SLR) approach based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to systematically examine and synthesize scholarly literature indexed in Sc-opus from Q1 to Q4 journals published within the last five years (2020–2024). A total of 103 scientific articles were analyzed using inclusion and exclusion criteria, thematic data extraction procedures, and content synthesis techniques. The findings reveal that transformational, visionary, and participative leadership styles positively contribute to enhancing employee engagement, voice behavior, and performance outcomes. Communicative, responsive, and empowering managerial support has been shown to improve employee productivity and well-being. Additionally, an ergonomic, digitally adaptive, and psychosocially supportive work environment significantly drives optimal performance outcomes. All exogenous variables demonstrate interconnected synergy through the mediating role of work motivation, which functions as a crucial psychological mechanism bridging structural influences and employee performance. These findings theoretically contribute to strengthening the frameworks of Transformational Leadership Theory, Job Demands–Resources Theory, Expectancy Theory, and the Resource-Based View (RBV). Furthermore, this study offers practical implications for organizations and proposes future research agendas emphasizing longitudinal approaches, cultural contextualization, and the integration of HR analytics. Keywords: Leadership Style, Managerial Support, Work Environment, Work Motivation, Employee Performance, Systematic Literature Review (SLR). Abstrak Penelitian ini bertujuan untuk menyusun kajian sistematik mengenai pengaruh gaya kepemimpinan, dukungan manajerial, dan lingkungan kerja terhadap kinerja karyawan, melalui motivasi kerja sebagai intervening. Pendekatan yang digunakan adalah Systematic Literature Review (SLR), dengan melakukan penyaringan dan sintesis literatur secara terstruktur dan sistematis. Sumber data berasal dari 103 artikel ilmiah terindeks Scopus, mencakup jurnal kuartil Q1 hingga Q4 dalam rentang lima tahun terakhir (2020–2024). Proses seleksi dilakukan menggunakan kriteria inklusi-eksklusi yang ketat, dilanjutkan dengan ekstraksi data tematik dan teknik sintesis konten. Hasil kajian mengungkapkan gaya kepemimpinan transformasional, visioner, dan partisipatif secara konsisten berkontribusi positif terhadap peningkatan employee engagement, voice behavior, dan performa kerja. Dukungan manajerial yang komunikatif, responsif, serta berorientasi pada pemberdayaan terbukti memperkuat produktivitas dan well-being karyawan. Selain itu, lingkungan kerja yang ergonomis, adaptif terhadap teknologi digital, dan suportif secara psikososial juga berperan signifikan dalam mendorong pencapaian kinerja optimal. Ketiga variabel eksogen tersebut menunjukkan hubungan sinergis yang dimediasi oleh motivasi kerja yang berfungsi sebagai mekanisme psikologis krusial dalam menjembatani pengaruh struktural terhadap outcome kinerja. Temuan ini memberikan kontribusi teoretis dalam memperkuat kerangka Transformational Leadership Theory, Job Demands-Resources Theory, Expectancy Theory, dan Resource-Based View (RBV). Selain itu, studi ini juga menawarkan implikasi praktis bagi organisasi dalam merancang strategi peningkatan kinerja berbasis sumber daya manusia, serta membuka ruang bagi agenda riset lanjutan yang mengintegrasikan pendekatan longitudinal, kontekstualisasi budaya, dan penerapan HR analytics. Kata Kunci: Gaya Kepemimpinan, Dukungan Manajerial, Lingkungan Kerja, Motivasi Kerja, Kinerja Karyawan.